THE USE OF COHESIVE DEVICES IN STUDENTS’ ARGUMENTATIVE ESSAYS - Afriani, Zelvia Liska (Linguists : Journal of Linguistics and Language Teaching, 2018)
This research aims at describing the use of cohesive devices in argumentative essay made by college students. The objectives of this research were to identify the most cohesion type the students used and to find out the percentage of all types and accuracy of cohesive devices. The design of this research was a descriptive quantitative research. The subject of this research was 36 students of the fifth semester; they were taken 50% for each class by using random sampling. The instrument of this research was writing test. The data were collected by using documentation method and were analyzed by using Halliday and Hasan theory for cohesion. The results of the study show that the most cohesion type that is frequently used is reference (44.3%), followed by lexical cohesion (39.6%), conjunction (14.8%), substitution (0.8%), and ellipsis (0.5%). In addition, the accuracy of the students in their essay can be seen from the percentages that ellipsis has the highest percentage (26.5%) followed by substitution (22.9%), reference (17.5%), lexical cohesion (17.1%), and conjunction (16%).